Pengaruh Pemahaman Konsep Matematis dengan Model Pembelajaran Contextual Teaching and Learning terhadap Hasil Belajar Siswa Kelas VII pada Materi Bentuk Aljabar - Sofiyani, Sofi; Yudhanegara, Mokhammad Ridwan (Universitas Batanghari Jambi, 2024)
This research was motivated by students' lack of understanding of mathematical concepts which affected student learning outcomes. This research aims to determine how much influence students' understanding of mathematical concepts with the Contextual Teaching and Learning learning model has on the learning outcomes of class VII students in algebra material. The research method used is a survey method using a test instrument of 5 questions and a questionnaire of 20 statements. With a sample size of 50 students, using random sampling techniques. In the normality and linearity test using Chi Square, and the multiple linear regression test, it was concluded that the data had a normal and linear distribution. In hypothesis testing using the coefficient of determination, an R square value of 0.883 was obtained. From this research it can be concluded that there is a significant influence between understanding mathematical concepts and the Contextual Teaching and Learning learning model on the learning outcomes of class VII students in algebra material.